METHODOLOGY OF THE ASSESSMENT FOR ALGORITHMIC COMPLEXITY OF PARALLEL IMPLEMENTATION OF THREE-DIMENSIONAL POLYADIC CODING - Рябуха, Ю. М. (Science-based technologies, 2015)
It outlines the main stages of building integration technology code designs the concept of formation of informative syntactic representation of segments in a processing system video informational resource (VIR) that provides: preset level of the semantic integrity and availability of information; reducing overhead, compatibility density syntactic and semantic segments. It is proved that the structure of the code representation of the video stream includes a four-level hierarchy, namely level of contoured video sequences, the level lines of the segments, the level of the individual segments and the level of the video frame. Develop methods of verification concepts VIR treatment considering their preliminary intellectual identification of the level of the semantic information content and the corresponding the syntactic density of coding. This provides next compatibility of the technological aspects of two concepts processing of static VIR concerning the support the implementation of the conditions of availability and integrity at the level of formation of informative components code designs syntactic description.